Malmö Treatment Referral and Intervention Study—High 12-Month Retention Rates in Patients Referred from Syringe Exchange to Methadone or Buprenorphine/Naloxone Treatment - Bråbäck, Martin; Ekström, Lars; Troberg, Katja; Nilsson, Suzan; Isendahl, Pernilla; Brådvik, Louise; Håkansson, Anders (Frontiers in Psychiatry, 2017)
Background: Heroin dependence is associated with high mortality. Opioid agonist treatment with methadone or buprenorphine has strong evidence for treatment of this relapsing condition. In our setting opioid agonist treatment has been associated with strict and demanding intake procedures, often with requirements of social stability, but also high, approximately 80 percent 12-months retention rates. In a recent randomized controlled trial (RCT) we demonstrated high rates of successful rapid referral from a syringe exchange programme (SEP) to treatment with methadone or buprenorphine, including actual treatment initiation. The objectives of this study were to assess 12-month retention rates, in order to assess whether a novel referral program of current drug users at a SEP would achieve retention rates comparable to more traditional intake procedures. Methods: The present report is a 12-month follow-up of 71 patients who successfully started treatment with methadone or buprenorphine/naloxone. Patient data from baseline and at 12 months was collected. Results: Out of the 71 patients who started treatment, 58 (82%) were still in treatment after 12 months. Conclusion: This was a population, referred from a SEP, with a high drug use severity on admission and no pre-treatment requirement for social stability, but there were still high retention rates at 12 months comparable to regular opioid agonist clinics in our setting.